2021
DOI: 10.2147/jmdh.s326846
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students’ Knowledge, Attitudes and Beliefs Regarding Molar Incisor Hypomineralization (MIH): A Survey in Vienna, Austria

Abstract: Purpose: Molar incisor hypomineralization (MIH) is a frequently encountered dental condition worldwide. The aim of this study was to evaluate the knowledge of Austrian dental students about MIH. Methods: A validated paper-based survey was distributed among 100 final year dental students at the Medical University of Vienna to assess their knowledge, perception and believes regarding MIH. One hundred dental students at the University Dental Clinic of Vienna were included in the study. At the time of the survey, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 28 publications
10
16
0
2
Order By: Relevance
“…Thence, not surprisingly, an overwhelming majority of them (89.4%) recommended that investigating the prevalence of MIH in Egypt would be worthwhile. These results support those in similar studies which have reported that practitioners are uncertain about the prevalence of MIH in their communities [ 19 21 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Thence, not surprisingly, an overwhelming majority of them (89.4%) recommended that investigating the prevalence of MIH in Egypt would be worthwhile. These results support those in similar studies which have reported that practitioners are uncertain about the prevalence of MIH in their communities [ 19 21 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies, nearly half of the students in the present study reported never seeing MIH-like defects in the second primary molars [ 18 , 19 , 21 ]. The other half reported observing MIH-like defects in the second primary molar less frequently than in FPMs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations